2008
DOI: 10.1143/jjap.47.891
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled c-Plane GaN Nanopillars on γ-LiAlO2 Substrate Grown by Plasma-Assisted Molecular-Beam Epitaxy

Abstract: We have grown M-plane GaN films with self-assembled C-plane GaN nanopillars on a -LiAlO 2 substrate by plasma-assisted molecular-beam epitaxy. The diameters of the basal plane of the nanopillars are about 200 to 900 nm and the height is up to 600 nm. The formation of self-assembled c-plane GaN nanopillars is through nucleation on hexagonal anionic bases of -LiAlO 2 . Dislocation defects were observed and analyzed by transmission electron microscopy. From the experimental results, we developed a mechanism under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…The MBE system was used to grow GaN nanorods on Si͑111͒ substrate, 23 GaN films on sapphire, 24 and nanopillars on ␥-LiAlO 2 . 25 When the nucleation of rectangular basal plane ͑M-plane͒ predominated that of hexagonal basal plane a͒ Electronic mail: ikailo@mail.phys.nsysu.edu.tw. In this study, we grew GaN epilayers on ␥-LiAlO 2 substrate in the absence of a low-temperature GaN buffer layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The MBE system was used to grow GaN nanorods on Si͑111͒ substrate, 23 GaN films on sapphire, 24 and nanopillars on ␥-LiAlO 2 . 25 When the nucleation of rectangular basal plane ͑M-plane͒ predominated that of hexagonal basal plane a͒ Electronic mail: ikailo@mail.phys.nsysu.edu.tw. In this study, we grew GaN epilayers on ␥-LiAlO 2 substrate in the absence of a low-temperature GaN buffer layer.…”
mentioning
confidence: 99%
“…The LiAlO 2 substrate, mounted on a rotating sample holder, was exposed to N 2 -plasma 10 min for nitridation at 500°C. 25 To check the crystal structure we performed x-ray diffraction ͑XRD͒ measurement focused on both central and side areas of these samples. From our previous study, we showed that the low ratio of N / Ga flux is favorable for 2D-like M-plane growth, while the high ratio leads to easier growth of three-dimensional ͑3D͒-like c-plane nanopillars.…”
mentioning
confidence: 99%
“…The two-orientation growth of GaN nanopillars on LAO substrate has been reported in our previous papers. 15,16 In this paper, we applied the two-orientation growth to the M-plane InN film and 3D c-plane InN hexagonal thin disks on LAO substrate with GaN and InGaN buffer layers. The crystal structure of the sample was characterized by the high-resolution X-ray diffraction (XRD) (Bede D1) measurements and showed in Fig.…”
Section: Analyses and Resultsmentioning
confidence: 99%
“…Recently, g-LiAlO 2 as an alternative substrate for GaN epitaxial growth has received a lot of attention [7][8][9][10][11][12][13]. LiAlO 2 crystal possesses a tetragonal structure with crystallographic P4 1 2 1 2 symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study suggests that III/V ratio is important to the epitaxial mechanisms on LiAlO 2 . For example, it was shown that in molecular beam epitaxy (MBE) growth, a high III/V flux ratio is favorable for 2D-like growth mode while a low III/V ratio precipitates 3D-like growth mode [9]. Hellman et al [10] used MBE to grow c-plane GaN on g-LiAlO 2 substrate.…”
Section: Introductionmentioning
confidence: 99%